The magic of the plain and the waters - Giraldo Alayza, Martha (1999)
"Everything is great there, In the pampas covered with grasslands thousands of sheep run like clouds... Even in its calamities the plateau is grandiose... Suddenly all of nature becomes cloudy, lightning appears followed by resounding thunder. Everything trembles terrifying... The lightning lights up like perennial torches and the hail resounds like a crash on all the flanks of the hills... But immediately, in an instant, in a second, everything is silent, the lightning and the hail stop; it makes a great silence in nature and a hole in the clouds lets filter the happy and invigorating sound... In winter the hills look like painter's palettes.